The role of the public in the management of public health risks - John Beard; Hudson Birden (Elsevier, 2004)
Abstract Objective: To critique current models of public involvement in the management of public health risks. Methods: Two case studies are used to highlight the challenges of contemporary practice. Results: Current models often result in affected communities having perceptions of risk that conflict with those responsible for risk management. This can lead to ineffective decision making. Conclusions: Involving the public throughout the risk assessment and risk management process may lessen conflict and result in better decisions. Implications: Those responsible for responding to public health risks should aim for transparent processes that highlight assumptions and uncertainties, and in volve the public wherever possible.